Zarit Caregiver Burden Interview: Psychometric Properties in Family Caregivers of People with Intellectual Disabilities - Domínguez-Vergara, Julio (2023)
Caregivers of people with intellectual disabilities may feel overburdened in their work and experience negative psychological consequences. The purpose of this instrumental study was to determine the evidence of internal structure and reliability of the Zarit Caregiver Burden Interview scale. A total of 398 family caregivers, including women and men, participated (M = 47.33, SD = 10.44). The structure of the scale was evaluated by factor analysis and the McDonald Omega coefficient was used to estimate reliability. Sixteen models of the scale were tested, differing in number of items and factor structures. A model of 15 items and 4 dimensions (overload, competence, social relationship, and interpersonal relationship) obtained acceptable fit (χ2 = 184.72; p < 0.001; CFI = 0.95; TLI = 0.94; RMSEA = 0.055; SRMR = 0.05) and reliability coefficients above 0.70 in their dimensions. It is concluded that the Zarit scale is valid and reliable for use in caregivers of people with intellectual disabilities.